2017
DOI: 10.3174/ajnr.a5126
|View full text |Cite
|
Sign up to set email alerts
|

Can MRI Visual Assessment Differentiate the Variants of Primary-Progressive Aphasia?

Abstract: BACKGROUND AND PURPOSE:Primary-progressive aphasia is a clinically and pathologically heterogeneous condition. Nonfluent, semantic, and logopenic are the currently recognized clinical variants. The recommendations for the classification of primary-progressive aphasia have advocated variant-specific patterns of atrophy. The aims of the present study were to evaluate the sensitivity and specificity of the proposed imaging criteria and to assess the intra-and interrater reporting agreements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 48 publications
3
21
1
4
Order By: Relevance
“…SD cases have hypometabolism and atrophy centred on the ATL bilaterally (Mummery et al, 2000), which data from other methods in healthy participants and patient groups has shown to be a key region for the formation of coherent concepts (Lambon Ralph et al, 2010). This finding agrees with Sajjadi et al (2017) who found that the atrophy patterns for SD were more easily distinguishable (high sensitivity and specificity) than the other forms of PPA.…”
Section: Discussionsupporting
confidence: 92%
“…SD cases have hypometabolism and atrophy centred on the ATL bilaterally (Mummery et al, 2000), which data from other methods in healthy participants and patient groups has shown to be a key region for the formation of coherent concepts (Lambon Ralph et al, 2010). This finding agrees with Sajjadi et al (2017) who found that the atrophy patterns for SD were more easily distinguishable (high sensitivity and specificity) than the other forms of PPA.…”
Section: Discussionsupporting
confidence: 92%
“…Table 2, at QL in 9 (patients 1-9) of the 18 (50%) cases, the HA were in the temporoparietal cortex and in limbic structures, in most cases bilaterally and predominantly in the left hemisphere, with the highest negative z score value mainly in the temporoparietal and temporal lateral cortex at QN. At QL in 6 of 18 (33.3%) patients (10)(11)(12)(13)(14)(15), the HA were in the frontoparietal and frontotemporal regions with the highest negative z score value at QN, in the prefrontal and temporal regions. However, in the remaining 3 of 18 (16.7%) patients (16)(17)(18) in whom the HA at QL appeared widespread and irregular in both cortical hemispheres, QN localized the highest z score negative value in the prefrontal and parietal areas bilaterally.…”
Section: Resultsmentioning
confidence: 95%
“…Diagnosis and classification of the different variants of PPA, namely nfvPPA, svPPA, and lvPPA, by clinical and neuropsychological analyses may be difficult; however, an early correct diagnosis allows adequate treatment, and influences disease progression as well as prognosis [6,[21][22][23]. Thus, it has been necessary to employ neuroimaging procedures as standard and functional MRI, the latter still limited [10,25,26]. Brain metabolic 18 F-FDG PET studies, using QL, have also been utilized with favorable results in the diagnosis of PPA and in the discrimination of the different variants [27].…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 2 more Smart Citations